A hidden aggregation‐prone structure in the heart of hypoxia inducible factor prolyl hydroxylase. Issue 5 (6th March 2016) - Hadi‐Alijanvand, Hamid; Proctor, Elizabeth A.; Ding, Feng; Dokholyan, Nikolay V.; Moosavi‐Movahedi, Ali A.
ABSTRACT: Prolyl hydroxylase domain‐containing protein 2 (PHD2), as one of the most important regulators of angiogenesis and metastasis of cancer cells, is a promising target for cancer therapy drug design. Progressive studies imply that abnormality in PHD2 function may be due to misfolding. Therefore, study of the PHD2 unfolding pathway paves the way for a better understanding of the influence of PHD2 mutations and cancer cell metabolites on the protein folding pathway. We study the unfolding of the PHD2 catalytic domain using differential scanning calorimetry (DSC), fluorescence spectroscopy, and discrete molecular dynamics simulations (DMD). Using computational and experimental techniques, we find that PHD2 undergoes four transitions along the thermal unfolding pathway. To illustrate PHD2 unfolding events in atomic detail, we utilize DMD simulations. Analysis of computational results indicates an intermediate species in the PHD2 unfolding pathway that may enhance aggregation propensity, explaining mutation‐independent PHD2 malfunction. Proteins 2016; 84:611–623. © 2016 Wiley Periodicals, Inc.